Evaluating the Clogging Phenomenon in Pervious Concrete from January 2015 to December 2022 - Teymouri, Ehsan; Wong, Kwong Soon; Rouhbakhsh, Masoud; Pahlevani, Mahdi; Forouzan, Mehdi (Civil and Sustainable Urban Engineering, 2023)
This study investigated the effects of clogging in Pervious Concrete (PC) from January 2015 to December 2022. Three different PC mixtures were used, which included coarse aggregate (4.75-9.5 mm), fine aggregate (0-20% weight of coarse aggregate), cement (340 kg/m3), and w/c ratio of 0.35. The samples were tested for compressive strength, permeability, and porosity. The best PC mixture containing 10% fine aggregate was selected for monitoring clogging over time. This mixture had a compressive strength of 24.7 MPa, permeability of 1.19 mm/s, and void content of 13.96%. A large-scale prototype of PC10 (10% of fine aggregate) measuring 3.5 m in length, 1.7 m in width, and 0.20 m in depth was constructed in Mashhad City, Iran. The in-place infiltration rate was measured on a monthly basis as the PC experienced different rainfall levels. The results showed that due to clogging, the infiltration rate was reduced by an average of 10% for the first four years of the experiments. This was followed by a substantial reduction of 20% in 2019 and 16.75% in 2020. Due to a high level of clogging, the infiltration rate was reduced by 5.02% and 2.23% in 2021 and 2022, respectively. However, the system still has the capacity to infiltrate at 1.14 mm/s. Although no maintenance was performed on the PC system, its efficiency and lifespan were substantially reduced. Nonetheless, the system can still be considered as an effective solution for stormwater management.